The Online Reputation of Tourism Brands and Their Dependence on Pandemic Scenarios: An Analysis of the "Hospederías De Extremadura" Brand before and during COVID-19 - SÁNCHEZ RIVERO, Marcelino; MURILLO GONZÁLEZ, Luis; RODRÍGUEZ RANGEL, María Cristina (Journal of Environmental Management and Tourism, 2022)
New technologies are having a decisive influence on the behaviour of tourists. Nowadays, all tourists search information on the internet before enjoying any service offered by tourism companies. Consequently, online reputation is an essential component in the marketing strategy of tourism brands. On the other hand, the Covid-19 pandemic has revolutionized tourism activity since its emergence in March 2020. Its direct effects have been widely studied in the literature, but no studies have yet been conducted on the effects of this pandemic on the online reputation of tourism brands. The aim of this paper is to empirically test whether this effect exists and if so whether it has been positive or negative. For this purpose, the weekly time series between January 2017 and September 2020 of ReviewPro's Global Review Index (GRI) were analyzed for 5 of the 8 accommodation which represent "Hospederías de Extremadura" tourism brand. To achieve the objectives of this paper, a pre-Covid period and a Covid period were considered and both the median values of the GRI and the trends in both periods have been compared. The results obtained demonstrate the disruptive character that the pandemic has had on the online reputation of tourism brands.